In-hospital neonatal mortality in a level-two hospital in Cape Town, South Africa - Gabriels, Cindi (Department of Paediatrics and Child Health, 2023)
Background Neonatal mortality (deaths in the first 28 days of life) is a major contributor to under-5 mortality in South Africa. Many advances in neonatal care have been introduced, but the impact of these interventions has not been studied outside of tertiary academic centers. Objectives To describe neonatal mortality in the neonatal high care unit at New Somerset Hospital in Cape Town, South Africa, over an 8 year period. Methods Neonatal deaths were captured and entered into a database; deaths were coded according to Perinatal Problem Identification Program categories. Results Neonatal deaths from 2011 to 2018 were analyzed, excluding 2014. There were 296 neonatal deaths; median birthweight of neonatal deaths was 1140g (interquartile range (IQR) 790 – 2420g); median gestation was 29 weeks (IQR 25 – 38). Immaturity (132/296, 45%) was the most common cause of death, followed by hypoxia (67/296, 23%) and infections (61/296, 21%). There were 250 (84%) neonatal deaths in the first week of life; there was a trend towards decreasing number of neonatal deaths (from 48 in 2011 to 34 in 2018), and rate of deaths (from 45.2 per 1000 admissions to 28.2 per 1000 admissions). This was driven by decreased deaths due to immaturity; number of deaths due to other causes remained approximately constant. Conclusions We observed decreasing number of neonatal deaths and rate of deaths per 1000 admissions, with the largest decrease due to prematurity. Advances in respiratory care for preterm neonates may have contributed to decreased mortality due to immaturity. Upstream obstetric interventions will be required to address hypoxia-related causes of neonatal mortality.